2022
DOI: 10.15698/cst2022.02.263
|View full text |Cite
|
Sign up to set email alerts
|

Building and breaking the gut barrier with bariatric surgery

Abstract: Bariatric surgery has been proposed to improve glycemic control in morbidly obese patients by stabilising the gut barrier and alleviating endotoxemia-induced insulin resistance. Here, recent studies are highlighted which reveal site-specific and at times opposing effects of bariatric surgery on the gut barrier. Further understanding the underlying mechanisms may not only inform the development of novel gut-based drugs for the initial treatment of type 2 diabetes, but possibly also assist in the management of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…On the other hand, transplanting colonic microbiota of RYGB-operated rats to germ-free mice improved oral glucose tolerance, possibly by stabilizing the intestinal epithelial barrier through increased bile acid receptor FXR signaling via the generation of secondary bile acids [39]. These findings suggest that the changes in gut microbiota and their associated metabolites after RYGB may have opposing effects on glycemic control, depending on the gut region [40]. For SG, cecal and fecal levels of the primary bile acid cholic acid-7 sulfate (CA7S) have been found to increase in mice and patients after surgery [41].…”
Section: Intestinal Milieumentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, transplanting colonic microbiota of RYGB-operated rats to germ-free mice improved oral glucose tolerance, possibly by stabilizing the intestinal epithelial barrier through increased bile acid receptor FXR signaling via the generation of secondary bile acids [39]. These findings suggest that the changes in gut microbiota and their associated metabolites after RYGB may have opposing effects on glycemic control, depending on the gut region [40]. For SG, cecal and fecal levels of the primary bile acid cholic acid-7 sulfate (CA7S) have been found to increase in mice and patients after surgery [41].…”
Section: Intestinal Milieumentioning
confidence: 93%
“…In mice treated with GDF15, there was a reduced preference for a high-fat diet [114]. Notably, RYGB-operated rats have increased circulating and portal vein GDF15 levels, and this is negatively correlated with their food intake and body weight [40]. While a separate study also showed increased circulating GDF15 levels and GDF15 protein in the gastric pouch, jejunum, and ileum of RYGB-operated rats [115], more data is needed to establish a causal link between gutderived GDF15 and the beneficial effects of BS [116,117].…”
Section: The Role Of the Hindbrain In The Hypophagic Effects Of Baria...mentioning
confidence: 99%